Portrayal of Military Operations of Pakistan in War on Terror by Leading American and British Newspapers - rehman, nazia; Rawan, Dr. Bakht (Journal of Peace, Development and Communication, 2022)
Mass media do not only portray the facts rather they play a significant role in construction of the facts by framing events/issues/ individuals .The present study was designed to explore the framing of Pakistan’s military operations in UK and USA press, which it took to uproot terrorism in the country. The researcher implied content analysis research methodology to examine portrayal. Online archives and newspaper subscriptions were accessed for data collection. The researcher deduced frames and developed exclusive and mutually exhaustive content categorization scheme to explore frames in pre and post operation period by implying content analysis method. The variation in use of frames by UK and US press was significant, however Conflict frame and international politics frame in pre operation time period and domestic Politics frame and Economic frame in post operation time period yielded insignificant difference as UK followed US policy on War on Terror. The study has found significant evidence about the influence of foreign policy and vested interest, on media image of a country as post operation coverage remained negative.